Aryl Radical‐Mediated Alkenylation of Alkyl Halides. Issue 8 (6th August 2019) - Chaambi, Ahmed; Kurtay, Gülbin; Abderrahim, Raoudha; Robert, Frédéric; Landais, Yannick
Abstract: The free‐radical alkenylation of a range of alkyl iodides with a vinyldisulfones has been carried out, leading to the desired vinylsulfones in moderate to good yields under mild conditions. The process is initiated by an aryl radical which abstracts the iodine atom from the alkyl iodide to form a C‐centered radical intermediate, the addition of which onto the vinyldisulfone providing the final vinylsulfone. The aryl radical is generated in situ through a single‐electron transfer from an electron donor‐acceptor complex (EDA) formed between a diaryliodonium salt (Ph2 I + PF6 − ) and triethylamine. Abstract :